Oxytocin as a treatment for high-risk psychosis or early stages of psychosis: a mini review - Bargiota, Stavroula I.; Papakonstantinou, Anna V.; Christodoulou, Nikolaos G. (Frontiers in Psychiatry, 2023)
Individuals at clinical high risk for psychosis (CHR-P) present as help-seeking individuals with social deficits as well as cognitive and functional impairment and have a 23%-36% risk of transition to first-episode psychosis. The therapeutic role of intranasal oxytocin (ΟΤ) in psychiatric disorders has been widely studied during the last decades, concerning its effects on social behavior in humans. A literature search was conducted via Pubmed and Scopus, using the search terms "oxytocin" and "psychosis". Six studies were included in the current review. There were differences in terms of demographics, intervention type, and outcome measures. ΟΤ may affect the social cognition skills of people at prodromal and early stages of psychosis, but its effect on clinical symptoms is ambiguous. Because of the high level of heterogeneity of existing studies, more original studies are needed to examine and clarify whether OT improves high-risk and early psychosis populations.